Modeling Stimulant and Opioid Co-use in Rats Provided Concurrent Access to Methamphetamine and Fentanyl - Seaman, Robert W.; Lordson, Chris; Collins, Gregory T. (Frontiers in Psychiatry, 2022)
Concurrent use of stimulants (e.g., methamphetamine) and opioids (e.g., fentanyl) has become increasingly common in recent years and continues to pose an enormous health burden, worldwide. Despite the prevalence, relatively little is known about interactions between the reinforcing effects of stimulants and opioids in this pattern of polysubstance abuse. The goals of the current study were to evaluate the relative reinforcing and relapse-related effects of methamphetamine and fentanyl using a concurrent access, drug-versus-drug choice procedure. Male Sprague-Dawley rats were first allowed to acquire self-administration for either 0.1 mg/kg/infusion methamphetamine or 0.0032 mg/kg/infusion fentanyl, independently, after which concurrent access to both drugs was provided. When training doses of methamphetamine and fentanyl were concurrently available, a subset of rats self-administered both drugs, either within a session or alternating across sessions, whereas the remaining rats responded exclusively for one drug. When the cost of the preferred drug was increased (i.e., unit dose reduced), or the cost of the non-preferred drug was decreased (i.e., unit dose increased), choice was largely allocated toward the cheaper alternative. Following extinction of responding, methamphetamine- and fentanyl-paired cues reinstated responding on both levers. Responding reinstated by a priming injection of methamphetamine or fentanyl allocated more responding to the lever previously reinforced by the priming drug. The current studies suggest that choice of methamphetamine and fentanyl is largely allocated to the cheaper alternative, although more co-use was observed than would be expected for economic substitutes. Moreover, they lay the groundwork for more fully evaluating interactions between commonly co-abused drugs (e.g., stimulants and opioids) in order to better understand the determinants of polysubstance abuse and develop effective treatment strategies for individuals suffering from a polysubstance use disorder.